Syntheses, crystal structures, optical, Raman spectroscopy, and magnetic properties of two polymorphs of NaMnPO4. (June 2020) - Jana, Subhendu; Lingannan, Govindaraj; Ishtiyak, Mohd; Panigrahi, Gopabandhu; Sonachalam, Arumugam; Prakash, Jai
Graphical abstract: Highlights: Monophasic natrophilite and maricite forms of NaMnPO4 were synthesized. Crystal structures of NaMnPO4 were confirmed by Rietveld refinements. Raman spectroscopy studies of NaMnPO4 were carried out. Optical bandgaps of NaMnPO4 polymorphs were determined. Magnetic studies confirm canted antiferromagnetism nature of the natrophilite form. Abstract: The monophasic natrophilite form of NaMnPO4 was synthesized using a simple and scalable one-step hydrothermal method. The heat treatment of the natrophilite NaMnPO4 in the air resulted in the formation of the high-temperature maricite polymorph of NaMnPO4 . The crystal structures of these two polymorphs were confirmed by the Rietveld refinements and Raman spectroscopy. The DSC study of the natrophilite form shows a broad exothermic peak indicative of a second-order phase transition to high-temperature maricite form. The band gaps ( Eg ) of 5.18(2) and 1.88(2) eV were estimated for natrophilite and maricite forms, respectively, by the UV–vis absorption studies. Magnetic studies on polycrystalline natrophilite NaMnPO4 show a complex temperature dependence of magnetic susceptibility, which could be attributed to a canted antiferromagnetic behavior with the Néel's temperature ( TN ) of 31 K and an anomaly temperature ( T* ) of 29 K. Maricite NaMnPO4 also show antiferromagnetic interaction of Mn 2+ spins with TN of 18 K.